Income inequality in general equilibrium - Bastien Bernon; Jozef Konings; Glenn Magerman (National Bank of Belgium, 2022)
We develop a quantitative framework in which income inequality arises endogenously in response to productivity shocks. The framework accommodates sectoral inputoutput linkages, arbitrary elasticities of factors and intermediates, and heterogeneous workers that endogenously choose to supply their labor across sectors. Workers are imperfectly mobile across sectors, parameterized by a Roy-Frechet setup. We characterize the impact of Harrod-neutral shocks and changes in labor mobility on income inequality and welfare up to first- and second order. Inequality arises in equilibrium due to a combination of changes in income share and labor use across all sectors due to their dependencies in the input-output network. We calibrate the model using Belgian data and provide quantitative results, confirming strong non-linearities. These results suggest that labor market-improving policies can have strong effects on both welfare and inequality, but the impact is both quantitatively and qualitatively dependent on the structure of the economy and its initial equilibrium.
Keywords: D24; D33; D50; D57; D63; E24; J31; 330; Income inequality; production networks; disaggregated macro models; wage gaps; mobility of workers; heterogeneous factors of production